European Resuscitation Council COVID-19 guidelines executive summary. (August 2020) - ,; Ainsworth, S.; Biarent, D.; Bingham, B.; Blom, M.T.; Borra, V.; Bossaert, L.; Böttiger, B.W.; Brissaud, O.; Carli, P.; Cassan, P.; Castrén, M.; et al.
Abstract: Coronavirus disease 2019 (COVID-19) has had a substantial impact on the incidence of cardiac arrest and survival. The challenge is to find the correct balance between the risk to the rescuer when undertaking cardiopulmonary resuscitation (CPR) on a person with possible COVID-19 and the risk to that person if CPR is delayed. These guidelines focus specifically on patients with suspected or confirmed COVID-19. The guidelines include the delivery of basic and advanced life support in adults and children and recommendations for delivering training during the pandemic. Where uncertainty exists treatment should be informed by a dynamic risk assessment which may consider current COVID-19 prevalence, the person's presentation (e.g. history of COVID-19 contact, COVID-19 symptoms), likelihood that treatment will be effective, availability of personal protective equipment (PPE) and personal risks for those providing treatment. These guidelines will be subject to evolving knowledge and experience of COVID-19. As countries are at different stages of the pandemic, there may some international variation in practice.